Investigating pupils’ perceptions of fieldwork approaches to history within the Malaysian integrated curriculum for secondary schools - Salleh, Mohamad Johdi; Mohamad, Baharom; Ambotang, Abdul Said (University Malaysia of Sabah, 2012)

(untitled)
This study was designed to evaluate fieldwork approaches to exploring history in the Integrated Curriculum for Secondary Schools (ICSS). Eight hundred Lower Secondary Schools pupils from the states of Perak and Terengganu were selected for the study using the convenience sampling method. The data gathered from the study was analysed using descriptive and inference statistics from the SPSS programme (Version 15). According to the results, more than ninety percent of the respondents agreed that the fieldwork method gave them an opportunity to “identify differences between the past and present” in Malaysian ICSS history. More positive responses were received from pupils in Perak than in Terengganu. Furthermore, the number of positive responses from science and regular schools were very high; boys and girls responded more-or-less equally, with Form Three being the most supportive. Responses according to ethnicity were also high. It is hoped that the findings of this study will enhance the teaching and learning of history through fieldwork as well as improving pupils’ overall academic performance.